Complexation reaction using ammonium based chloride compounds for preparation of eutectic mixtures. - Shamsuri, Ahmad Adlie; Abdullah, Dzulkefly Kuang (Canadian Center of Science and Education, 2011)
In this study, we are interested in the eutectic processing of chloride compounds, and decided to focus on ammonium based compounds that can provide sufficient insight in the fundamental chemistry. 14 types ammonium based chloride compounds namely ammonium chloride, methanaminium chloride, dimethylammonium chloride, trimethylammonium chloride, tetramethylammonium chloride, dodecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, carboxytrimethylmethanaminium chloride, phenyltrimethylammonium chloride, benzyltrimethylammonium chloride, (vinylbenzyl)trimethylammonium chloride, 2-acetoxytrimethylethanaminium chloride, (2-acetoxypropyl)trimethylammonium chloride and 2-(benzoyloxy)trimethylethanaminium chloride were used in this study. This research led to a hypothesis that the ammonium based chloride compounds could be react with the urea by complexing the hydrogen groups that are hydrogen bond donor giving eutectic mixtures. However, functional groups have plays an important role to influence thermal properties of those eutectic mixtures. This is regarded to be a motivating finding that will be important to most future research work involving complexation reaction for the production of eutectic mixtures.